Beyond the left cerebral hemisphere: bilateral language lateralization in healthy aging and its clinical implications - David Toloza-Ramirez; David Toloza-Ramirez; Rodrigo Santibañez; Leonardo Arraño-Carrasco; Romina Zunino-Pesce; Teresa Julio-Ramos; David A. Copland; Camilo Quezada; Carolina Mendez-Orellana; Carolina Mendez-Orellana; Carolina Mendez-Orellana (Frontiers in Aging Neuroscience)
BackgroundFunctional MRI (fMRI) studies conducted on young adults reveal a predominantly left-lateralized cortical language network during semantic and phonological processing (SP and PP, respectively). Both linguistic dimensions have been advanced as potential cognitive markers of pathological aging. However, the neural mechanisms underlying SP and PP among healthy older adults remain poorly understood.AimThis study aimed to investigate the dynamics of language lateralization among native Spanish-speaking older adults in relation to their behavioral performance in specific semantic and phonological tasks.MethodologyTwenty-eight healthy, right-handed older Chilean adults (mean age: 67.7, SD±: 7.44, range: 60–87) took part in an fMRI session during which they performed semantic and phonological tasks. They were also evaluated for overall language performance using the Spanish version of ScreeLing and verbal fluency tasks. A fixed-effect analysis was performed to explore group-level differences. Standard regression analyses were also used to assess the association between brain activation and language performance.ResultsBoth SP and PP elicited bilateral activation in the pars triangularis and opercularis of the inferior frontal gyrus (IFG) and the superior temporal gyrus. Activation was also observed in the left inferior parietal gyrus. Semantic fluency performance was significantly associated with activation in the right angular gyrus and the pars opercularis of the IFG. In contrast, phonological fluency was associated with bilateral activation in the IFG pars orbitalis.ConclusionAmong healthy older adults, SP and PP recruit bilateral language-related brain regions, potentially reflecting compensatory mechanisms associated with normal aging. Notably, the IFG pars orbitalis may play a distinct role in supporting phonological fluency, despite not being a region traditionally linked to PP. Further research is needed to clarify the contribution of this region to phonological performance among aging adults.